Matched Cohort Analysis of the Effect of the Facial Recess Approach on Cerebrospinal Fluid Leak After Translabyrinthine Surgery for Schwannoma. Issue 9 (October 2021) - Christopher, Laura; Slattery, William; Lekovic, Gregory P.; Mehta, Gautam U.; Miller, Mia
Abstract : Objective: The facial recess approach during translabyrinthine surgery has been used to expose the eustachian tube (ET) for packing. We sought to determine the effect of this technique on the development of postoperative nasopharyngeal cerebrospinal fluid (CSF) leaks. Patients: Cohorts of patients with cerebellopontine angle schwannomas who underwent a facial recess approach or no facial recess approach were matched based on tumor size. Interventions: Translabyrinthine surgery for tumor resection. Main Outcome Measures: Postoperative CSF leaks were recorded and nasopharyngeal CSF leaks were utilized as the primary outcome measure. Results: Using an exact matching protocol based on tumor size, 102 patients were included in each group (204 total, 111 female, 93 male). Overall, 9 patients (4.4%) demonstrated a postoperative nasopharyngeal CSF leak. Postoperative CSF rhinorrhea was noted in 3.9% of the group who underwent a facial recess approach for packing of the ET and 4.9% of the group who did not undergo a facial recess approach. This rate was not significantly different between groups ( p = 0.99, Odds ratio: 0.79, 95% CI: 0.15–3.8). Secondary variables including age, tumor size, a diagnosis of NF2, and the packing material used were not significant predictors of nasopharyngeal CSF leaks. Conclusions: CSF rhinorrhea is infrequent after translabyrinthine surgery. The incidence of this complication is not affected by whether or not a facial recess approach is performed during surgery to pack the ET. Based on these data, use of this technique should be based on surgeon comfort and preference.